Partisipasi Masyarakat dalam Upaya Mengatasi Abrasi Pantai di Desa Modapuhi Kecamatan Mangoli Utara Kabupaten Kepulauan Sula - Darling Surya Alnursa (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesia is an archipelagic country characterized by a maritime state with 176 regencies and 30 cities, out of about 368 regencies and cities that have coastal and marine areas. Indonesia itself has the fourth longest coastline in the world after Canada, America and Russia, with a coastline of 95,181 km. However, as much as 20% of the coastline along the territory of Indonesia was reported to be damaged, of course this damage was caused by several factors, including environmental changes and coastal abrasion. This research was conducted in Modapuhi Village, North Mangoli District, Sula Islands Regency. The method used in this study is a survey method with qualitative research and structured interview techniques. Qualitative research is a research procedure that produces descriptive data in the form of written written words from people and observable behavior.